Integrable Structure of Multispecies Zero Range Process - Kuniba, A.; Okado, M.; Watanabe, S. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
We present a brief review on integrability of multispecies zero range process in one dimension introduced recently. The topics range over stochastic R matrices of quantum affine algebra Uq(An⁽¹⁾), matrix product construction of stationary states for periodic systems, q-boson representation of Zamolodchikov-Faddeev algebra, etc. We also introduce new commuting Markov transfer matrices having a mixed boundary condition and prove the factorization of a family of R matrices associated with the tetrahedron equation and generalized quantum groups at a special point of the spectral parameter.